Blue-yellow emissive LaAlO3:Dy3+ phosphor for high bright white light-emitting diodes - Tung, Ha Thanh; Dang, Huu Phuc (Institute of Advanced Engineering and Science, 2023)
LaAlO3:Dy3+ (LAO:Dy3+) with blue-yellow emission for brilliant white light of light-emitting diodes (LEDs) was prepared using gel-combustion process. The chemical content of the created material was confirmed using energy dispersive X-ray analysis (EDX). The transmission electron microscopy was used to examine the phosphor crystal size and morphology. The luminescence analysis showed that LAO:Dy3+ phosphors exhibited peaks at 482 nm (blue) and 574 nm (yellow), attributed to the transitions 4F 9/2à6H 15/2 and 4F 9/2à6H 13/2, respectively. The investigating of correlated color temperature (CCT) and Commission International de L'Eclairage (CIE) described that the phosphor LAO:Dy3+ helped to attained good CCT coordination and bright cool-white emission under ultraviolet (UV) stimulation. However, when using in white LED fabrication, the concentration of LAO:Dy3+ should be modified to fulfill the need from manufactures. According to results from this work, the white light luminescence intensity and color rendering performance may be reduced if the LAO:Dy3+ is high (10%) because of too much scattering. On the other hand, such scattering improvements offered by LAO:Dy3+ phosphor is beneficial to reduce the color deviance for better color uniformity of light.